Secrets and shadows - Chick, Bryan (New York Greenwillow Books, 2011)
Noah and his friends in the Secret Society join forces with four teens known as the Descenders to try to protect the Secret Zoo hidden below the Clarksville City Zoo from monstrous sasquatches and the evil Shadow Master
Ages 9-12
1
Keywords: Friendship -- Fiction; Mystery and detective stories; Sasquatch -- Fiction; Zoo animals -- Fiction; Zoos -- Fiction